Etika dalam Mitos dan Legenda Islam: Menggali Kearifan Tradisional - Annisa Ningtias (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2024)
This journal delves into the ethical aspects within Islamic myths and legends as a reservoir of rich moral and ethical values. This research employs an interdisciplinary approach, combining literary, religious, and ethical studies to understand the depth and relevance of the traditional wisdom embedded in Islamic myths and legends. By analyzing ancient narratives and epic stories within the Islamic heritage, this study illustrates that ethics is not just an abstract concept but a guiding principle reflected in ancient stories. The results of this research reveal the complexity of ethics in various contexts of Islamic myths and legends, encompassing values such as honesty, wisdom, courage, and compassion. In-depth analysis of tales like "The Story of Ali Baba" and "The Story of Prophet Solomon" highlights how these values are interwoven within the narratives and provide ethical guidance for readers. This study stimulates contemplation on how Islamic communities can tap into the wealth of ethics within their cultural heritage to guide their actions and decisions in everyday life. In conclusion, this journal emphasizes the importance of integrating traditional wisdom into contemporary ethical studies.